Preterm infant with diprosopus and holoprosencephaly. Issue 12 (22nd December 2021) - Nair, Nitya M.; Swarr, Daniel T.; Barnes‐Davis, Maria E.
Abstract: Diprosopus is an extremely rare congenital anomaly involving craniofacial duplication. The etiology and pathophysiology remain unknown, and no genetic mutations have been definitively associated with the condition. This case describes an infant born at 27‐weeks completed gestation with multiple congenital anomalies including diprosopus and discusses the implications of prenatal diagnosis.